A 3D, Magnetically Actuated, Aligned Collagen Fiber Hydrogel Platform Recapitulates Physical Microenvironment of Myoblasts for Enhancing Myogenesis. Issue 6 (13th May 2021) - Shi, Nianyuan; Li, Yuhui; Chang, Le; Zhao, Guoxu; Jin, Guorui; Lyu, Yi; Genin, Guy M.; Ma, Yufei; Xu, Feng
Abstract: Many cell responses that underlie the development, maturation, and function of tissues are guided by the architecture and mechanical loading of the extracellular matrix (ECM). Because mechanical stimulation must be transmitted through the ECM architecture, the synergy between these two factors is important. However, recapitulating the synergy of these physical microenvironmental cues in vitro remains challenging. To address this, a 3D magnetically actuated collagen hydrogel platform is developed that enables combined control of ECM architecture and mechanical stimulation. With this platform, it is demonstrated how these factors synergistically promote cell alignment of C2C12 myoblasts and enhance myogenesis. This promotion is driven in part by the dynamics of Yes‐associated protein and structure of cellular microtubule networks. This facile platform holds great promises for regulating cell behavior and fate, generating a broad range of engineered physiologically representative microtissues in vitro, and quantifying the mechanobiology underlying their functions. Abstract : A 3D, magnetically actuated collagen hydrogel platform enables combined control of extracellular matrix architecture and mechanical stimulation, which can effectively recapitulate the synergy of these physical microenvironmental cues of myoblasts in vitro. Synergistic effects of aligned fiber and mechanical stretch enhance C2C12 cell alignment and myotube formation. This facile platform holds great promises for generating physiologically representative microtissues for biomedical applications.